The Effectiveness of Dhikr Therapy and the Happy Menopause Booklet on Sleep Quality of Premenopausal Women - Listiana, Eka; Fatikhah, Fatikhah; Rejeki, Sri (Indonesian Journal of Global Health Research, 2024)
Premenopause occurs due to decreasing levels of the hormones estrogen and progesterone produced by the ovaries, this decrease causes changes in a woman both psychologically and physiologically. During the transition from premenopause to menopause, women will experience disturbances and sleep disturbances, causing a decrease in sleep quality. This study aims to see the effect of dhikr therapy and the happy menopause booklet on the sleep quality of premenopausal women. This study used a quasi-experimental design with a pre and posttest with a control group with a sample of 100 women. This research was carried out for eight weeks with a frequency of three times per week (Tuesday, Thursday, Saturday) with a duration of 15-20 minutes before going to bed at night. The intervention given was that respondents read the book on happy menopause then continued reading the dhikr Al-Fatihah, Al-Ikhlas, Al-Falaq, dhikr repeated 3 times for each letter, reading tasbih, tahmid, takbir repeated 33 times. Researchers used data collection tools to measure sleep quality with the Pittsburgh Sleep Quality Index (PSQI). The results showed that dhikr therapy and the happy menopause booklet could improve sleep quality in premenopausal women with an p value of 0.000. Premenopausal women are advised to do it regularly to improve sleep quality.